(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
This study investigates the implementation of hibah within the Takaful operations of AIA Public Berhad in Malaysia, focusing on the issues and challenges encountered. Hibah, a voluntary transfer of wealth or benefits, is increasingly being integrated into Takaful (Islamic insurance) as a mechanism to distribute surplus funds among participants. However, its implementation within AIA Takaful presents numerous challenges, including navigating complex regulatory frameworks, aligning with Shariah principles, and addressing operational constraints. Employing a qualitative approach, this research draws on in-depth interviews with industry experts to gather insights into the practical application of hibah in AIA Takaful. The study examines the roles of Takaful operators, the perceptions and expectations of customers, and the broader implications of hibah for Islamic finance in Malaysia. It also highlights the societal impact of hibah, considering its potential to enhance social welfare and financial inclusion. The findings contribute to a deeper understanding of the critical issues that impede the effective implementation of hibah in AIA Takaful and offer recommendations to overcome these challenges. By shedding light on these obstacles, this research aims to facilitate the more widespread and effective use of hibah in the Takaful industry.